Noninvasive quantification of intrarenal allograft C4d deposition with targeted ultrasound imaging. Issue 1 (27th September 2018) - Liao, Tao; Zhang, Yannan; Ren, Jie; Zheng, Haofeng; Zhang, Hongjun; Li, Xiujie; Liu, Xiaonan; Yin, Tinghui; Sun, Qiquan
Abstract : Antibody‐mediated rejection (AMR) has emerged as a major cause of renal allograft dysfunction. C4d, a specific marker for AMR diagnosis, was strongly recommended for routine surveillance; however, currently, C4d detection is dependent upon tissue biopsy, which is invasive and provides only local semi‐quantitative data. Targeted ultrasound imaging has been used extensively for noninvasive and real‐time molecular detection with advantages of high specificity and sensitivity. In this study, we designed C4d‐targeted microbubbles (MBC4d ) using a streptavidin‐biotin conjugated method and detected C4d deposition in vivo in a rat model of AMR by enhanced ultrasound imaging. This noninvasive procedure allowed successful acquisition of the first qualitative image of C4d deposition in a wide renal allograft section, which reflected real‐time C4d distribution in grafts. Moreover, we introduced normal intensity difference for quantitative analysis, which exhibited a nearly linear correlation with the grade of C4d deposition according to pathologic analysis. In addition, this approach showed no influence on survival rates and pathologic features in the microbubble injection groups, thereby demonstrating its safety. These findings demonstrated a simple, noninvasive, quantitative, and safe evaluation method for C4d, with the utility of this approach potentially preventing patients from having to undergo an invasive biopsy. Abstract : This study establishes a noninvasive, comprehensive, and quantitative method for detecting C4d deposition in renal allografts through targeted ultrasound imaging.